EARLY CHILDHOOD’S TEACHERS’ PERFORMANCE IN IMPLEMENTING DEVELOPMENT ACHIEVEMENT LEVEL STANDARD - Muchtar, Hendi Suhendraya; Yanuarsari, Revita; Lestari, Zubaedah Wiji (PEOPLE: International Journal of Social Sciences, 2016)
The increase of public awareness on the importance of Early Childhood Education (EDC) signed by numbers of establishment on non-formal early childhood institutions organized by society. However, this situation is not in accordance with the existance of sufficient qualified teachers. The aim of this study is to describe and inform early childhood education teachers’ performance. The method used in this study is descriptive analytic method. The data collection techniques are interviews, observations, and documentation study. The participant were chosen purposively, they were two managers and three early childhood teachers. From the findings, it was found that most of early childhood teachers performance were still not optimum. It was happened due to misperceptions of early childhood teachers in developing curriculum. The finding shows that: 1) lesson plan, method and instructional media development were arranged inappropriately 2) the syllabus was only made in form of daily and weekly planning, 3) the ratio between teachers and children were imbalance, 4) teachers were pay more attention on the final result, and 5) teachers emphasize on the development of basic skills. From those findings, it can be concluded that mostly the barriers faced by early childhood teachers largely influenced by external factors.